2009
DOI: 10.1016/j.physbeh.2009.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated re-entrainment to advanced light cycles in BALB/cJ mice

Abstract: Circadian rhythms in mammals are coordinated by the suprachiasmatic nuclei (SCN) of the hypothalamus, which are most potently synchronized to environmental light-dark cycles. Large advances in the light-dark cycle typically yield gradual advances in activity rhythms on the order of 1-2 hours per day until re-entrainment is complete due to limitations on the circadian system which are not yet understood. In humans, this delay until re-entrainment is accomplished is experienced as jetlag, with accompanying sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…*p < 0.05. female mice, which lasts about 7 days. Such transient shift of behavioral rhythms to a new LD cycle has already been well characterized in male mice and it has been shown that adaptation is a gradual process and requires multiple transient circadian cycles of 5 to 7 days following a 6-to 8-h phase advance of the LD cycle (Honma et al, 1985;Legates et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…*p < 0.05. female mice, which lasts about 7 days. Such transient shift of behavioral rhythms to a new LD cycle has already been well characterized in male mice and it has been shown that adaptation is a gradual process and requires multiple transient circadian cycles of 5 to 7 days following a 6-to 8-h phase advance of the LD cycle (Honma et al, 1985;Legates et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, when Npas2 expression is low, Per2 and Rev-erb-␣ expression will be high because of the feedback inhibitory mechanism of circadian gene expression. Traditionally, in most animal models of circadian gene expression, animals will be sacrificed at specific time points to determine the phase of gene expression levels over a 24-h period (47)(48)(49)(50). However, in our primate model, this is not technically feasible.…”
Section: Mrna Copy Number Of Circadian Genes From Fetal Liver Shows Tmentioning
confidence: 99%
“…We therefore asked whether the liver circadian epigenome would reentrain to the light-dark cycle after a week (Recovery Group), a time point shown by others (LeGates et al, 2009; Kiessling et al, 2010; Summa et al, 2012) to be sufficient for behavioral reentrainment, as defined by locomotor activity rhythms. We verified in identical conditions that locomotor activity reentrains within a week after a 6-h phase advance (Fig.…”
Section: Resultsmentioning
confidence: 99%